2012
DOI: 10.1175/jcli-d-11-00206.1
|View full text |Cite
|
Sign up to set email alerts
|

Central-West Argentina Summer Precipitation Variability and Atmospheric Teleconnections

Abstract: The interannual-to-multidecadal variability of central-west Argentina (CWA) summer (October–March) precipitation and associated tropospheric circulation are studied in the period 1900–2010. Precipitation shows significant quasi cycles with periods of about 2, 4–5, 6–8, and 16–22 yr. The quasi-bidecadal oscillation is significant from the early 1910s until the mid-1970s and is present in pressure time series over the southwestern South Atlantic. According to the lower-frequency spectral variation, a prolonged w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 43 publications
0
32
0
1
Order By: Relevance
“…In the eastern margin of the domain analysed, there is a strong consensus concerning the progressive increase up to the present of annual rainfall mainly due to the increases in rainfall during the summer (de Barros Soares et al, ; Saurral et al, ). Whereas to the southwest, the region underwent a sudden rise in summer precipitation by mid‐1970s owing to the influence of the 1976/1977 climate transition (Agosta and Compagnucci, ), which caused the shift towards the west of the agricultural barrier of the humid Pampas (border between the humid and semi‐arid regions). However, these precipitation trends seem to have reversed after the early 2000s (Maenza et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In the eastern margin of the domain analysed, there is a strong consensus concerning the progressive increase up to the present of annual rainfall mainly due to the increases in rainfall during the summer (de Barros Soares et al, ; Saurral et al, ). Whereas to the southwest, the region underwent a sudden rise in summer precipitation by mid‐1970s owing to the influence of the 1976/1977 climate transition (Agosta and Compagnucci, ), which caused the shift towards the west of the agricultural barrier of the humid Pampas (border between the humid and semi‐arid regions). However, these precipitation trends seem to have reversed after the early 2000s (Maenza et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The climate shift is coincident with a phase change of the PDO index, which has determined a ‘La Niña‐like’ decadal regime before and an ‘El Niño‐like’ decadal regime afterwards (Ebbesmeyer et al ., ; Mantua et al ., ; Solomon et al ., ). Furthermore, given the outstanding magnitude of the mid‐1970s shift, Jacques‐Coper and Garreaud () agreed with Agosta and Compagnucci () that the climate shift effects on southern South America climates seem to be unprecedented during the 20th century. In our analysis, we have found that the equatorial Pacific basin also plays a relevant role in regulating precipitation variability at interannual scale during the long‐term dry period observed from the 1920s to the 1960s, and during the transitional epoch related to the climatic shift in the mid‐1970s.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Such a climate favours grape production under irrigation to such an extent that this is the main grape‐growing region in Argentina (Agosta et al ., ). The relationship between the NC summer precipitation variability and the tropospheric circulation at interannual scale has been intensively examined by Agosta and Compagnucci (, ). The bi‐decadal oscillation in the NC summer precipitation results in alternating wet and dry spells, lasting approximately 9 years each, from the early 1900s until the early 1970s (Compagnucci et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…From 1973 to the early 2000s, a wet spell is observed perturbing the bi‐decadal oscillation towards lower frequencies. As a consequence of the extended wet spell, the regionally averaged precipitation undergoes an increase of about 24% in the last decades (Agosta and Compagnucci, ). The precipitation increment is in agreement with the changes in the frequency of the principal modes associated to the synoptic tropospheric circulation in southern South America resulting from the 1976/1977 climate transition (Agosta and Compagnucci, ).…”
Section: Introductionmentioning
confidence: 98%